The effects of different biofertilizers on the vegetative growth of potted rice plants / Izzuddin Ali - Ali, Izzuddin (Faculty of Plantation and Agrotechnology, 2015)
Application of biofertilizers are able to increase soil fertility and the effectiveness used of fertilizer. Biofertilizers give positive effects on paddy growth performance by increasing the nutrients available in the soil. Arbuscular mycorrhizal fungi and Trichoderma spp. give better growth performance by colonising rhizosphere of host plant and provide nutrient. Plant-microbes interaction will enhanced the fertilizer-use efficiency. The objective of this study was to evaluate the effects of different biofertilizers on paddy growth under pot conditions. Arbuscular mycorrhizal fungi and Trichoderma spp. were used in this study either alone or in combination. Two weeks old seedlings were transplanted to the field soil under a pot. Paddy that were inoculated with arbuscular mycorrhizal fungi had better plant height, number of tiller and phosphorus content after 9 weeks after sowing. Conversely, shoot and root biomass were not significantly influenced by AMF and Trichoderma spp. Colonization under pot conditions. We conclude that the AMF inoculation during transplanting increased plant height, number of tiller and phosphorus content.